Psycho-Emotional and Behavioral Problems in Children With Growth Hormone Deficiency - Aryayev, Mykola; Senkivska, Liudmyla; Lowe, John B. (Frontiers in Pediatrics, 2021)
Objective: to identify psycho-social problems and self-esteem in children with growth hormone deficiency (GHD) and define the role of some clinical and socio-demographic determinants in the conceptualization of internalizing and externalizing problems as criteria for psycho-social functioning. Materials and methods. A GHD sample (46 prepubescent children) was selected and compared to a matched control group ( 80 healthy children). Psycho-social functioning in children with GHD was investigated using the A. Goodman's “Strengths and Difficulties Questionnaire (SDQ)”. The study of children's self-esteem was carried out by the Dembo-Rubinstein method. Results. This study reveals that the GHD sample has more internalizing problems and lower self-esteem.  Higher score and frequency of assessment in the abnormal score for “total difficulties”, “emotional problem”, “peer problem” were found in children with GHD. The SDQ score and the frequency of assessment in the abnormal score for all SDQ scales in children with more pronounced growth deficit (height SDS <−3) did not exceed the same indicators in children with less growth retardation (−3 < height SDS <−2). Comparison of psycho-social features in children with isolated growth hormone deficiency and multiple pituitary hormones deficiency did not reveal differences in SDQ score and the frequency of assessment in the abnormal score for all SDQ scales. It was found that children with GHD have a reduced level of assertions, low self-esteem and a weak discrepancy between the level of assertions and self-esteem. Some socio-demographic determinants (male gender, age <9 years, low family income) and clinical determinants (low compliance, suboptimal growth response after 1 year of rGHh therapy) have an impact on the overall assessment of psychological problems in children with GHD. The internalizing difficulties are associated with certain clinical determinants (growth status, treatment status) and socio-demographic determinants (female gender, age < 9 years). Conclusions. The identification of low self-esteem and the high SDQ score for scales “total difficulties”, “emotional problems” and “peer problems” indicates psycho-socіal maladjustment and conceptualization of internalizing problems in children with GHD.